2004
DOI: 10.1016/s0886-3350(04)00539-5
|View full text |Cite
|
Sign up to set email alerts
|

Corneal edema and intraocular pressure after cataract surgery*1Randomized comparison of Healon5 and Amvisc Plus

Abstract: Both OVDs were beneficial in a wide range of cataract patients. However, the results suggest a tendency toward a higher complication rate with Healon5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Two eyes (4%) had IOP spikes greater than 30 mm Hg, which needed treatment with beta blocking agents. Moser et al 14 noticed IOP spikes greater than 30 mm Hg at day 1 in 10% of patients with Healon5 (NaHa 2.3%) and in 2.9% with Amvisc Plus (NaHa 1.6%). In another comparison between Healon (NaHa 1%), Healon GV (NaHa 1.4%), and Healon5, Arshinoff and coauthors 15 observed IOP spikes R30 mm Hg in 11.11% of the overall eyes during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Two eyes (4%) had IOP spikes greater than 30 mm Hg, which needed treatment with beta blocking agents. Moser et al 14 noticed IOP spikes greater than 30 mm Hg at day 1 in 10% of patients with Healon5 (NaHa 2.3%) and in 2.9% with Amvisc Plus (NaHa 1.6%). In another comparison between Healon (NaHa 1%), Healon GV (NaHa 1.4%), and Healon5, Arshinoff and coauthors 15 observed IOP spikes R30 mm Hg in 11.11% of the overall eyes during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough removal of OVD is recommended, since residual OVD remaining in the eye is a likely cause of IOP elevation. 735 Dispersive OVDs are more likely than cohesive OVDs to be retained in the eye because they adhere to intraocular structures such as the cornea, iris, and IOL. The optimal pharmacological regimen for preventing an immediate postoperative IOP spike is unclear.…”
Section: P33mentioning
confidence: 99%
“…The increase in IOP may be attributable to various causes, including inflammation, pigment dispersion, ophthalmic viscosurgical device retention blocking aqueous outflow, greater vascular permeability with increasing protein concentrations, and residual lens or iris debris (17-19).…”
Section: Discussionmentioning
confidence: 99%
“…The IOP spikes mainly occur soon after surgery and disappear after 24 hours; however, as the majority of patients undergo outpatient surgery, the spikes occur after they have been discharged. The increase in IOP may be attributable to various causes, including inflammation, pigment dispersion, ophthalmic viscosurgical device retention blocking aqueous outflow, greater vascular permeability with increasing protein concentrations, and residual lens or iris debris (17)(18)(19) Comparing different concentrations of topical b-blocker spikes should be avoided even in nonglaucomatous eyes because they can cause corneal edema and pain and, if they continue for longer than 24 hours, may cause optic nerve damage; most patients undergoing cataract surgery are elderly and, as they may have impaired retinal and optic nerve circulation, even a slight increase in IOP can damage optic nerve fibers (24). A number of drugs have been investigated as possible means of controlling IOP spikes after cataract surgery but, although some of these may reduce the early postoperative increase in IOP, most have a number of limitations (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%